2019
DOI: 10.18632/aging.101989
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl cysteine, inulin and the two as a combined therapy ameliorate cognitive decline in testosterone-deprived rats

Abstract: Our previous studies reported that testosterone-deprived rats developed cognitive decline as a result of increased brain oxidative stress, microglia hyperactivity, and hippocampal dysplasticity. In addition, gut dysbiosis occurred in these rats. Previous studies demonstrated that n-acetyl cysteine (NAC) and a prebiotic (inulin) improved cognition in several pathological conditions. However, its effects on cognition in the testosterone-deprived condition have never been investigated. This study hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Previous research found that oligofructose-enriched inulin in the diet (5%, w/w) produced relaxing-like effects and improved learning functions in animal models . A combination of N -acetyl cysteine and inulin has been reported to help with cognitive decline in a testosterone-deprived rat model . Recent studies also demonstrated that inulin could reduce HFD-induced neuroinflammation and anxiety .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that oligofructose-enriched inulin in the diet (5%, w/w) produced relaxing-like effects and improved learning functions in animal models . A combination of N -acetyl cysteine and inulin has been reported to help with cognitive decline in a testosterone-deprived rat model . Recent studies also demonstrated that inulin could reduce HFD-induced neuroinflammation and anxiety .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that inulin improves mood as well as memory and digestion in humans [ 17 ]. Inulin also ameliorates castration-induced cognitive decline [ 18 ]. Unexpectedly, although long-term (6 months) supplementation of inulin (7.5%) improves metabolic syndrome in toll-like receptor 5 (TLR5)-knockout mice, many of these mice develop icteric hepatocellular carcinoma (HCC) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, the hippocampus is a critical structure for memory formation (Denninger et al, 2018;Vogel-Ciernia & Wood, 2014). We have found that HFD-induced prediabetes impaired hippocampaldependent cognitive function (Chunchai et al, 2019;Jinawong et al, 2020). As the aim of this study is to determine the effect of L6H21 and metformin on hippocampal-dependent cognitive function at different time points, it is important to select the effective cognitive function test that must reflect the hippocampal-dependent cognitive function in a short time period.…”
Section: Determination Of Cognitive Function By Nol Test In Combinati...mentioning
confidence: 99%
“…Sample sizes subjected to statistical analysis included eight rats per group, which were estimated from G*Power program (Version 3.1.9.4). The effect size calculation was determined on the basis of our previous study (Chunchai et al, 2019). The group size in this study represents independent values, and the statistical analysis was done using these independent values.…”
Section: Data and Statistical Analysismentioning
confidence: 99%